Development and validation of the HIV adolescent readiness for transition scale (HARTS) in South Africa. Issue 7 (8th July 2021) - Zanoni, Brian C; Archary, Moherndran; Sibaya, Thobekile; Musinguzi, Nicholas; Kelley, Mary E; McManus, Shauna; Haberer, Jessica E
Abstract: Introduction: Adolescents living with perinatally acquired HIV have low rates of retention in care and viral suppression after the transition from paediatric to adult care. In this study, we developed and validated a tool to identify adolescent transition readiness. Methods: We developed the HIV Adolescent Readiness for Transition Scale (HARTS) from June 2016 to May 2019 by iteratively adapting existing transition readiness scales for other chronic illnesses by conducting focus groups with 11 healthcare providers and 20 adolescents in South Africa. We administered a preliminary questionnaire to 131 adolescents to determine psychometric properties and assess test–retest variability. We used confirmatory factor analysis to verify the proposed scale structure using the underlying variable approach. We correlated responses to self‐described transition readiness and age using linear regression. We subsequently validated the scale by prospectively administering it to 199 adolescents in a second South African setting before their transition. We then used multivariable logistic regression to assess the effects of the HARTS and relevant socio‐behavioural covariates on viral suppression one year after transition. Results: We identified four domains relevant to transition readiness: disclosure, health navigation, self‐advocacy and health literacy. Fifteen questions with a significant factor loading of 0.3 to 0.9 were identified. No significant test–retest variability was seen among 10% of participants. Positive correlations with self‐described transition readiness were significant with the overall HARTS and domains of health navigation, self‐advocacy and health literacy. In the prospective analysis, for adolescents not using drugs, each 10‐point increase in the HARTS was associated with 0.62 odds of viral failure (95% CI 0.45 to 0.86; p  = 0.004). The individual domains of self‐advocacy (AOR 0.56; 95% CI 0.33 to 0.94; p  = 0.029), disclosure (AOR 0.02; 95% CI 0.01 to 0.25; p  = 0.002), health navigation (AOR 0.51; 95%CI 0.25 to 1.02; p  = 0.056) and health literacy (AOR 0.37; 95% CI 0.10 to 1.30; p  = 0.121) were associated with viral failure adjusting for age at antiretroviral therapy initiation, ART regimen, sex, disclosure status, and alcohol use in both analyses. Conclusions: The HARTS is a validated scale that can be used to identify which adolescents may require additional interventions prior to transitioning to adult care to improve viral suppression after transition.